Signal changes on MRI and increases in reactive microgliosis, astrogliosis, and iron in the putamen of two patients with multiple system atrophy. Issue 1 (January 1996) - Schwarz, J; Weis, S; Kraft, E; Tatsch, K; Bandmann, O; Mehraein, P; Vogl, T; Oertel, W H
Abstract : A correlation of clinical, MRI, and neuropathological data is reported in two patients with multiple system atrophy (MSA). On MRI, patient 1 showed striatal atrophy, reduction of T2 relaxation times within most of the putamen, and a band of hyperintense signal changes in the lateral putamen. In patient 2, MRI disclosed only shortening of the T2 signal in the putamen. Immunohistochemistry showed pronounced reactive microgliosis and astrogliosis in the affected brain regions. In patient 1, the area with the most pronounced microgliosis and astrogliosis most likely correlated with the area of hyperintense signal changes on MRI. This area also contained the highest amount of ferric iron, which was increased in the putamen of patient 1 but not patient 2. It is unlikely that the hypointense signal changes in the putamen are due to an increase of iron alone. Reactive microglial and astroglial cells may play a part in the pathogenesis of MSA.